Latent trajectories of change for clients at a psychodynamic training clinic. Issue 7 (28th February 2019) - Jankowski, Peter J.; Sandage, Steven J.; Bell, Chance A.; Rupert, David; Bronstein, Miriam; Stavros, George S.
Abstract: Objective: Employing practice‐based research methods, we addressed the need to examine the effectiveness of psychodynamic treatment as a supplement to the efficacy evidence offered by randomized clinical trials. Method: We used person‐centered analyses to generate latent subgroups of clients ( N  = 118; M age  = 40.92; 53.4% female; 81.4% Caucasian; 80.5% heterosexual) receiving contemporary relational psychotherapy (CRP) at a psychodynamic community mental health training clinic. Results: Subgroups of clients reported a change in depression, social conflict, and anxiety symptomatology, and overall life satisfaction, depicted by significant quadratic growth curves. Findings also offered exploratory support for a theoretical proposition from CRP that improved relational functioning would correspond to improved affect dysregulation and overall life satisfaction. Conclusion: Clinical and training implications highlight the need to distinguish subgroups of "responders" and "nonresponders" to inform treatment.